THE ROLE OF-MUSIC IN CHILD DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article reveals the important role of music education in the development of the moral and aesthetic sphere of the childs personality. By fostering moral feelings, we lay the foundation for the formation of his moral consciousness, the regulation of moral behaviour in the future.